PRELIMINARY PHYTOCHEMICAL ANALYSIS OF TABERNAEMONTANA ALTERNIFOLIA - SELVAKUMAR SIVAGNANAM; ARVIND KUMAR (International Journal of Pharma and Bio Sciences, 2014)
Medicinal plants are an important source of phytochemicals that offers traditional medicinal treatment of various ailments. Phytomedicinal constituents can be derived from any part of the plant like bark, leaves, fruits, flowers, roots, seeds etc. The herbal medicines are becoming more popular because of its inability to cause side effects and cheaper than synthetic drugs. Phytochemical is chemical compounds that occur naturally in plants. Phytochemistry deals with the chemical structure, biosynthesis, metabolism, natural distribution and biological function. Phytochemical studies have attracted the attention of plant scientists due to the development of new and sophisticated techniques. This can be sorted by their chemical class, bio synthetic origin and functional groups into primary and secondary metabolites. The study and analysis of chemical constituents of plants are desirable, not only for the discovery of therapeutic agents, but also for disclosing new resources of such chemical substances. Therefore it is of interest to investigate the phytochemical analysis of aqueous chloroform, acetone, aqueous ethanolic, ethyl acetate and aqueous extracts Tabernaemontana alternifolia.